2022
DOI: 10.3390/ijms23031616
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein as a Biomarker for Major Depressive Disorder?

Abstract: The etiopathogenesis of depression is not entirely understood. Several studies have investigated the role of inflammation in major depressive disorder. The present work aims to review the literature on the association between C-Reactive Protein (CRP) and depression. A systematic review was performed for the topics of ‘CRP’ and ‘depression’ using the PubMed database from inception to December 2021. Fifty-six studies were identified and included in the review. Evidence suggested the presence of dysregulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 142 publications
2
36
1
Order By: Relevance
“…Inflammation, or inflammatory reaction, is caused by the activation of the immune system, usually characterized by local reactions caused by stimulation, injury, or infection, accompanied by symptoms such as redness, swelling, heat, and pain ( 6 ). Redness, swelling, heat, and pain were commonly associated with local reactions caused by stimulation, injury, or infection ( 7 ). In patients with severe depression, the abnormal expression of glucocorticoid receptors is related to inflammation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, or inflammatory reaction, is caused by the activation of the immune system, usually characterized by local reactions caused by stimulation, injury, or infection, accompanied by symptoms such as redness, swelling, heat, and pain ( 6 ). Redness, swelling, heat, and pain were commonly associated with local reactions caused by stimulation, injury, or infection ( 7 ). In patients with severe depression, the abnormal expression of glucocorticoid receptors is related to inflammation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…44 A recent systematic review from 56 studies provides robust evidence about the potential role of CRP in the development of adult MDD. 45 Finally, it has been proposed that the co-occurrence of obesity and MDD may have a genetic basis. For example, association study has revealed that NPY2R gene was associated with both childhood obesity and adulthood MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a heightened inflammatory response is linked to MDD. Specific proinflammatory cytokines and their receptors associated with MDD include interleukin (IL)-6, tumor necrosis factor (TNF)-α, IL-1β, IL-2, IL-2 receptor, IL-4, IL-10, the IL-1 receptor antagonist, the transforming growth factor-β, and C-reactive protein (CRP) [ 127 , 128 ]. Proinflammatory cytokines also correlate with MDD symptom severity [ 129 ] and CRP with treatment-response [ 130 ].…”
Section: Molecular Pathways and Systemsmentioning
confidence: 99%